Principales enfermedades que se presentan en el cultivo de sandía (Citrullus lunatus) en el Ecuador - Valdez Morante, Nelson Andrés (2022)
In general, in watermelon cultivation and production, one of the major constraints is the presence of various pests and diseases, mainly diseases caused by fungi and viruses, which are widespread in all watermelon producing areas of Ecuador, with high negative impact on production, with known cases of losses of up to 80%. The virus with the greatest impact on the watermelon crop is Cucumber and Watermelon Mosaic Virus (CMV), followed by Watermelon Mosaic Virus (WMV-1) and Zucchini Yellow Mosaic Virus (ZyMV). In view of this problem, we have alluded, in general, to the integrated control of pests and diseases, combining cultural measures, disinfection of tools, prevention and control of insect vectors such as whiteflies, thrips, aphids, elimination of nearby weeds and in the crop, the use of entomophagous insects such as Bemisia, the preparation and use of organic insect repellent liquids, and preventive application of specific fungicides to combat watermelon diseases. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about the main diseases that occur in the watermelon crop (Citrullus lunatus) in Ecuador